Effects of different areca nut chewing habits on the gut microbiota of mice: High‐throughput sequencing analysis. Issue 1 (23rd October 2018) - Zhao, Ziwei; Wu, Zhongkun; Wang, Chuanhua; Cheng, Huan; Yi, Shuhan; Li, Ke; Li, Zongjun; Wang, Yuanliang
Abstract: The chewing of areca nut is closely associated with human diseases such as oral submucous fibrosis and immune related diseases. Recent studies have focused on the pharmacological and toxicological effects of areca nut chewing, and have largely overlooked the effects on intestinal microbiota. In this study, we sought to understand how different methods of areca consumption affect intestinal microflora composition. A total of 60 male and 60 female Kunming mice were each randomly divided into six groups and fed different areca preparations to mimic different areca nut chewing habits. The preparations included fresh areca fruit; areca fruit with betel leaf or cured tobacco; brined areca; smoked brined areca; and a control. The fecal microbiota of mice in the 12 groups was compared after 28 days of oral gavage administration. To determine the composition and diversity of the fecal microbiota, we performed high‐throughput sequencing of bacterial 16S rRNA. In both male and female mice, the diversity and abundance of the intestinal microbiota of the experimental groups were higher than those in the control groups. Furthermore, different areca preparations had different effects on the diversity, abundance, and composition of the intestinal flora of Kunming mice. Practical applications: The chewing of areca nuts in various forms is widespread in Asia and other areas. This manuscript first explores the effects of different areca nut chewing habits on the gut microbiota of mice. We then further clarify the impact of different areca nut chewing habits on intestinal health and provide a new direction for areca nut research. In addition, our findings will increase public understanding of areca nut usage and provide guidance for the areca nut industry.